Lunotriquetral Coalition - Mertens, Kris; Mespreuve, Marc; Vanhoenacker, Filip M. (Seminars in Musculoskeletal Radiology, 2023)
Lunotriquetral (LT) coalition is the most common carpal coalition. Four morphological types of LT coalition have been described. LT coalition is usually asymptomatic, but rarely a fibrocartilaginous type may cause ulnar wrist pain. We report a case of bilateral asymptomatic LT coalition that was seen incidentally on conventional radiography taken after a wrist injury. Conventional radiography is the first imaging technique to detect and classify this type of LT coalition. Magnetic resonance imaging is a useful tool to investigate possible associated pathology of the carpal joints, particularly if surgical treatment of a symptomatic patient is anticipated.
Keywords: lunotriquetral coalition; computed tomography; carpal bones; conventional radiography; magnetic resonance imaging